Emotion Regulation Strategies and Sense of Life Meaning: The Chain-Mediating Role of Gratitude and Subjective Wellbeing - Lin, Zhengzheng (Frontiers in Psychology, 2022)
This study aimed to explore the mechanism of college students’ meaning of life. The Emotion Regulation Questionnaire,the Gratitude Questionnaire Six-Item Form, the General Well-being Schedule ,the Meaning in Life Questionnaire were used to survey 1312 college students (Mage = 19.26, SD = 1.15). The results showed that (1) the cognitive reappraisal and expression suppression strategies were significantly positively and negatively correlated with gratitude, subjective well-being, and the sense of life meaning, respectively. (2) The former indirectly predicted the sense of life meaning through the chain mediation of gratitude → subjective well-being. (3) Further, the expression suppression strategy indirectly predicted college students’ meaning of life through the chain intermediary of gratitude → subjective well-being. This study illuminated the roles of emotion regulation strategy, gratitude, and subjective well-being in influencing the sense of life meaning among the Chinese college students.